A social realist account of the way academic managers exercise agency in monitoring students' academic success in South African higher education - Dwayi, Valindawo Valile Medicine (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
The roots of this thesis lie in discourses which promote the use of academic monitoring strategies for student success in South African higher education. Although access to higher education widened for black South Africans following the first democratic election, this 'formal' access (Morrow, 1993) has not been matched by success with annual cohort studies showing that, regardless of the university at which they are registered, the subjects they are studying and the qualifications they hope to attain, black South Africans fare less well than their white peers. Monitoring performance and referring students on to academic support and development structures thus became a strategy identified as having the potential to address patterns in performance data. The study reports on an attempt to introduce a strategy for Academic Monitoring for Integrated Academic Development at a historically black university in South Africa's Eastern Cape province. It draws on a metatheoretical framework developed from Bhaskar's (1978, 1998) critical realism and Archer's (1995, 1996) social realism to do this. More specifically, it focuses on the way managers at the institution exercised their agency in relation to the strategy and identifies the way social and structural conditions, developed from the time colonial settlers first arrived on the continent, worked to constrain the exercise of this agency. Although the focus of the study was on agency, the study revealed a system of necessary contradictions (Archer, 1995, 1996), a system of conflicting beliefs exacerbated by a lack of resources, that led to the implementation of the strategy not being as successful as intended. The study not only illuminates the conditions at one South African university but also adds to the body of work on management in higher education and to critiques of 'managerialism'.,Eyona ngxam yale thisisi kukuphendla iindlela zokukhuthaza ukusetyenziswa kwamaqhinga ezemfundo okuqwalasela impumelelo yabafundi kumaziko emfundo ephakamileyo aseMzantsi Afrika. Nangona emva konyulo lokuqala lwedemokhrasi abemi abantsundu baseMzantsi Afrika bethe bavuleleka ukuba bafikelele kwimfundo ephakamileyo, olu fikelelo 'lusesikweni' (Morrow, 1993) khange luhambelane nempumelelo yaba bafundi, nanjengoko uphando olujolise kwimpumelelo yabafundi ngonyaka ngamnye lubonisa ukuba aba bafundi bathi nokuba bafunda kweyiphi iyunivesithi, befunda ziphi iikhosi bekwafundela waphi amakhono, abafundi abantsundu basoloko berhuqeka emva xa bethelekiswa nabo bamhlophe. Ukuqwalaselwa kwenkqubela nokudluliselwa kwabafundi kumacandelo enkxaso nophuhliso kwimiba yemfundo kube liqhinga elithe lachongwa njengelunokukwazi ukujongana neepateni zendlela abaqhuba ngayo abafundi. Olu phando lunika ingxelo malunga nenzame yokuza neqhinga lokuQwalaselwa kwemiba yeMfundo ukwenzela uPhuhliso kwiyunivesithi eyayisakuba yeyabantsundu kwiphondo leMpuma Koloni laseMzantsi Afrika. Luqamele ngesakhelo semethathiyori esakhelwe kwi-critical realism kaBhaskar (1978, 1979) kunye ne-social realism kaArcher (1995, 1996). Eyona nto lugxile kuyo yindlela abalawuli neenkokeli zeli zikomfundo eziwasebenzisa ngayo amagunya azo ngokunxulumene neli qhinga, lukwachonga indlela iimeko zentlalo nezeziko, ezamana ziphuhliswa ukususela oko kwathi kwafika abarhwaphilizi kweli lizwekazi, ezasebenza ngayo ekunqandeni ukusetyenziswa kwala magunya. Nangona ugxiliso lolu phando belusemagunyeni, luthe lwaveza uluhlu lwemiba echaseneyo eyimfuneko (Archer, 1995, 1996), uluhlu lweenkolelo ezingqubanayo ezihlutshezwa kukushokoxeka kwezixhobo, nolukhokelele ekubeni ukufezekiswa kweli qhinga kungabiyiyo le mpumelelo ibilindelekile. Olu phando aluphelelanga nje ekugqamiseni iimeko zale yunivesithi yaseMzantsi Afrika, koko lukongeza kumsebenzi osele wenziwe kwimfundo ephakamileyo lukwaphendla 'ezolawulo'.
Keywords: Social realism -- South Africa -- Eastern Cape; Critical realism; New public management; Academic development; Academic achievement -- South Africa -- Eastern Cape; College students Rating of -- South Africa -- Eastern Cape; College student development programs -- South Africa -- Eastern Cape; Student adjustment -- South Africa -- Eastern Cape